Overcoming resistance to PD-1 and CTLA-4 blockade mechanisms and therapeutic strategies - Wang, Xiaodong; He, Jing; Ding, Gouping; Tang, Yixuan; Wang, Qianqian (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) targeting PD-1 and CTLA-4 have achieved groundbreaking clinical success in multiple cancers; however, a large proportion of patients experience primary or acquired resistance. This review synthesizes the complex mechanisms underlying resistance to PD-1/CTLA-4 blockade and surveys emerging strategies to overcome them. Resistance arises from multifaceted interactions among tumor-intrinsic alterations (e.g., epigenetic silencing of antigen presentation machinery via EZH2/PRC2, oncogenic pathway–driven upregulation of PD-L1, genetic loss of IFNγ pathway components such as JAK1/2 or B2M), immune cell dysfunction (e.g., T cell exhaustion with co-expression of inhibitory receptors including PD-1, TIM-3, and LAG-3, metabolic and epigenetic T cell reprogramming, suppressive regulatory T cells), and stromal microenvironmental factors (e.g., hypoxia-inducible factors, immunosuppressive metabolites like IDO-mediated kynurenine, tumor-associated macrophages and MDSCs, aberrant angiogenesis). To counteract these diverse resistance mechanisms, a spectrum of novel therapeutic approaches is under development. Mechanism-targeted monotherapies include agents that restore tumor immunogenicity (e.g., epigenetic modulators to upregulate MHC expression), reinvigorate exhausted T cells (e.g., blockade of alternative checkpoints such as LAG-3), and reprogram the suppressive tumor microenvironment (e.g., inhibitors of immunosuppressive myeloid pathways). In parallel, rational combination therapies are being explored, pairing ICIs with chemotherapy (to induce immunogenic cell death and enhance T cell infiltration), molecularly targeted drugs (to disrupt oncogenic immune-evasion signals), or immune modulators (e.g., IL-2 or IL-18 variants to boost effector T cell function). Furthermore, emerging predictive biomarkers and machine learning-based signatures (e.g., soluble checkpoint levels, inflammatory indices, tumor transcriptomic scores) are improving the ability to anticipate ICI resistance and guide personalized escalation of therapy. Overall, this synthesis highlights the recent insights into resistance biology and promising avenues to extend the durable benefits of PD-1/CTLA-4 blockade to a larger proportion of patients.